2010
DOI: 10.1016/j.exger.2010.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA repair and association with aging – An update

Abstract: Mitochondrial DNA is constantly exposed to oxidative injury. Due to its location close to the main site of reactive oxygen species, the inner mitochondrial membrane, mtDNA is more susceptible than nuclear DNA to oxidative damage. The accumulation of DNA damage is thought to play a critical role in the aging process and to be particularly deleterious in post-mitotic cells. Thus, DNA repair is an important mechanism for maintenance of genomic integrity. Despite the importance of mitochondria in the aging process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
124
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(128 citation statements)
references
References 155 publications
1
124
0
2
Order By: Relevance
“…Numerous studies have demonstrated that oxidative stress damage of mainly mtDNA may be the factor responsible for triggering those adverse effects (2,19,20,22,23,33,45). Chatterjee et al (5) demonstrated that mitochondrially targeted mutant OGG1 resulted in more cell death than nuclear-targeted mutant OGG1 upon exposure of cells to oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have demonstrated that oxidative stress damage of mainly mtDNA may be the factor responsible for triggering those adverse effects (2,19,20,22,23,33,45). Chatterjee et al (5) demonstrated that mitochondrially targeted mutant OGG1 resulted in more cell death than nuclear-targeted mutant OGG1 upon exposure of cells to oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…mtDNA damage can trigger a series of events such as decreased transcription and incomplete assembly of the electron transport chain (ETC) complexes, which leads to decreased ETC activity and thus lower ATP synthesis, increased ROS production, and apoptosis (9,14). 8-Hydroxy 2=-deoxyguanine (8-OHdG) is one of the most common ROS-induced DNA lesions and is considered an index of DNA damage (19,27). High levels of mitochondrial 8-OHdG have been correlated with increased mutation, deletion, fragmentation, and loss of mtDNA (28,31,42).…”
mentioning
confidence: 99%
“…16). Also, accumulation of damage to the mitochondrial genome is central in the mitochondrial theory of aging (1,20,22). DNA repair serves to reduce accumulation of mutations in mtDNA, but the mechanisms of mtDNA repair are not nearly as well understood as those of nuclear DNA repair.…”
Section: Perspectives and Significancementioning
confidence: 99%
“…Recurrent forward and backward mutations make neutral fixation impossible (Wright 1931;Feller 1951;Valenzuela 2000Valenzuela , 2002aValenzuela et al, 2010). Mutations do occur in mtDNA of eukaryote organisms during their life and are a main factor in aging and death (Gredilla et al, 2010). As well, hundreds of human mtDNA mutations are known that produce lethal or sub-lethal conditions (Tuppen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%